DETEKSI PARASIT MALARIA PADA DARAH DONOR DI UNIT DONOR DARAH PALANG MERAH INDONESIA CABANG KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Wimarti, Oktri Yetta; ", Fatmawati; Maryanti, Esy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Malaria is one of transfusion-transmitted disease. Transfusion-transmittedmalaria has a high potential risk in endemic area. One of endemic area in RiauProvince is Indragiri Hilir Regency. This research was descriptive study withcross sectional design to detect malaria parasites in blood donors at BloodDonors Unit of Indonesian Red Cross Society of Indragiri Hilir Regency. Thesamples were 45 and they were choiced by simple random sampling techniquewhen blood donation activity by mobile unit and regular service schedule ofBlood Donors Unit of Indonesian Red Cross Society of Indragiri Hilir Regency.The detection of malaria parasites used antigen detection with Inostic test kit andmicroscopic examination method with thin and thick smears with Giemsastaining. Detection of malaria parasites showed frequency of malaria positive andfrequency of malaria based on species and stage in blood donors were 0 (0%).Key words : malaria, malaria infection by transfusion, blood of donors,malaria antigen, microscopic malaria.